Peran Korps Brimob Polri Dalam Penanggulangan Pelanggaran Hukum oleh Geng Motor di Mako Brimob Polda Sumatera Utara - Aldyan Teoly Telaumbanua; Marlina Marlina; M. Citra Ramadhan (Mahesa Research Center, 2021)
This paper aims to examine the rule of law regarding law violations by motorcycle gangs, to examine the role of the Brimob Police Corps and the obstacles faced in overcoming law violations by motorcycle gangs. The problem is focused on how the law rules regarding law violations by motorcycle gangs, what is the role of the Brimob Police Corps and the obstacles faced in overcoming law violations by motorcycle gangs. To approach this problem, Soerjono Soekanto's role theory is used. The data were collected through interview guidelines and analyzed qualitatively. This study concludes that the criminal act of violating the law by motorcycle gangs is contrary to Article 170 regarding crimes against public order, Article 351, Article 352, Article 368 regarding persecution and Article 510 and Article 511 regarding violations of public order in the Criminal Code, contrary to Article 106 and Article 115 in the Law of the Republic of Indonesia Number 22 of 2009 concerning Road Traffic and Transportation. The role of the Brimob Police Corps in overcoming violations of the law by motorcycle gangs can be seen by using Soerjono Soekanto's theory based on aspects of role as a norm, role as an individual/norm, and role in the social structure of society. The constraint factors faced by Brimob are that the perpetrators of violations are minors, the lack of parental supervision of their children and the actions of motorcycle gangs usually involve a large number of people.